Termination of Taxi Rental Purchase Agreement Between Members of Pandawa Taxi Cooperative and PT Bank Bri Persero Unit Pudakpayung Yogyakarta - Rizky, Baharian (Jurnal Konstatering, 2024)
An agreement or contract must meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. The purpose of this study is to determine and analyze the termination of the taxi rental purchase agreement between members of the Pandawa Taxi Cooperative and PT Bank BRI Persero Unit Pudakpayung Yogyakarta and the legal consequences of the termination of the taxi rental purchase agreement between members of the Pandawa Taxi Cooperative and PT Bank BRI Persero Unit Pudakpayung Yogyakarta. The approach method in this study is empirical legal research. The types of data in this study are primary data and secondary data obtained from library research and field research and analyzed qualitatively with descriptive methods. The results of the study concluded that the responsibility of the management of the Pandawa Taxi Cooperative as a guarantor if the cooperative member is in default is based on the cooperation agreement between the Pandawa Taxi Cooperative and PT Bank BRI Persero Unit Pudakpayung Yogyakarta with the settlement of the default committed by the cooperative member will be resolved.